Method for detecting micro-nano plastic based on light-induced enhanced Raman spectroscopy
Through the Fe3O4@PH light-induced enhancement Raman spectroscopy method, combined with AgNPs and NaCl solutions for light-induced aggregation, the problems of low spatial resolution of MNPs detection and interference in the pretreatment of sample in the prior art were solved, and qualitative and quantitative analysis of MNPs were achieved.
Patent Information
- Application Number
- CN202411867371.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-04
AI Technical Summary
The detection of micro-nano plastics (MNPs) in the prior art has limitations such as low spatial resolution and interference in sample pretreatment, which leads to difficulties in qualitative and quantitative analysis.
Using Fe3O4@PH light-induced enhanced Raman spectroscopy (PIERS) method, the MNPs were adsorbed by Fe3O4@PH magnetic microspheres, and combined with AgNPs and NaCl solution for light-induced aggregation and Raman detection, to achieve qualitative and quantitative analysis of MNPs.
This method achieves high sensitivity detection of polyethylene nanoplastics (PE-NPs) and polypropylene nanoplastics (PP-NPs) in aqueous solution, with detection limits of 5 and 10 μg/mL, respectively, and can identify MNPs in bottled drinking water, tap water, seawater and digested human tissue suspension.
Smart Images

Figure CN119757314A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of micro-nano plastic detection, and specifically relates to a method for detecting micro-nano plastic based on light-induced enhanced Raman spectroscopy. Background Art
[0002] With the continuous use of plastic products, microplastics (MPs) and nanoplastics (NPs) have been widely detected in the atmosphere, water and soil. Due to the small size, high stability, and difficulty in degradation of micro-nanoplastics (MNPs), and their accumulation and transformation in ecosystems and food chains, they pose a huge threat to the ecological environment, food quality and safety, and human health. The pollution detection and prevention of MNPs has become a hot area of scientific and public concern.
[0003] However, there is still a lack of standard detection methods for MNPs in environmental and food samples, so there are few studies on the accurate concentration of NPs in ecosystems. Many early works studied the effects of NPs on human health through laboratory-scale experiments, in which engineered NPs were used as models. Compared with MPs, the properties of NPs and their biological, ecological and human health effects may be more complex and ambiguous. Studies have also shown that NPs may be the least known but most dangerous marine debris and endanger human health. Detection techniques for NPs in environmental and food samples should be developed and improved, which will facilitate the study of the effects of NPs on ecosystems as well as human health.
[0004] Currently, the most commonly used identification methods for MNPs are Fourier transform infrared spectroscopy (FTIR) and traditional Raman spectroscopy; however, due to the limited diffraction resolution of the instruments, the spatial resolution of FTIR and Raman spectroscopy is theoretically 20 μm and 1 μm, respectively, so the spatial resolution of these two methods may not be able to achieve the detection of nanoparticles.
[0005] Additionally, sampling, handling, and identification of MPs and NPs are problematic as these particles vary in size, color, density, and have additives (such as colorants and plasticizers) that make detection even more challenging. Summary of the invention
[0006] [Technical issues]
[0007] Existing technologies for the detection of MNPs have limitations such as low spatial resolution and interference from sample pretreatment, which makes it more difficult to perform accurate qualitative and quantitative analysis of MNPs.
[0008] [Technical solution]
[0009] In view of the shortcomings of the prior art for detecting MNPs, the purpose of the present invention is to provide a method for detecting MNPs based on photoinduced enhanced Raman spectroscopy; the method has the characteristics of high efficiency, economy, less interference and high accuracy.
[0010] In order to achieve the above purpose, the technical solutions provided are as follows:
[0011] The present invention provides a method for qualitatively detecting MNPs in a sample based on Fe3O4@PH photoinduced enhanced Raman spectroscopy (PIERS), the method comprising the following steps:
[0012] (1) Preparation of samples to be tested
[0013] The Fe3O4@PH magnetic microspheres are added to the sample solution to be tested and stirred, and then the Fe3O4@PH magnetic microspheres adsorbed with MNPs are collected under an external magnetic field, dried, and the dried Fe3O4@PH magnetic microspheres adsorbed with MNPs are diluted with ultrapure water to form a dilution solution;
[0014] (2) Qualitative analysis of samples to be tested
[0015] The diluted solution obtained in step (1) is mixed with the AgNPs suspension and the NaCl solution to form a mixed solution; the mixed solution is dropped onto a glass slide for light induction, and Raman detection is performed after drying;
[0016] Based on the KnowItAll software, the acquired Raman spectra were paired with the standard reference Raman database, and spectra with a similarity of more than 70% with the standard reference spectra were screened, indicating the presence of MNPs in the sample.
[0017] In one embodiment, the stirring conditions in step (1) are: 100-300 rpm, 30-60 min.
[0018] In one embodiment, the drying conditions in step (1) are: 40-60° C., and the drying time is 8-24 hours.
[0019] In one embodiment, the dilution with ultrapure water in step (1) is as follows: after mixing the dried Fe3O4@PH magnetic microspheres adsorbed with MNPs, dilute them with ultrapure water at a solid-liquid ratio of 1:2, mg:mL.
[0020] In one embodiment, the sample to be tested is any one of bottled drinking water, tap water, sea water, and a suspension of a digested human tissue sample.
[0021] In one embodiment, the preparation of the Fe3O4@PH magnetic microspheres in step (1) comprises the following steps:
[0022] 1) Preparation of Fe3O4 microspheres
[0023] FeCl3·6H2O, ammonium acetate (NH4Ac), sodium citrate and ethylene glycol are mixed in a flask, and mechanically stirred to completely mix to obtain a yellow solution; the yellow solution is sealed in a high-pressure reactor to react; after the reaction, it is cooled, washed, magnetically separated and dried to obtain Fe3O4 microspheres;
[0024] 2) Preparation of Fe3O4@PDA microspheres
[0025] Take the magnetic Fe3O4 microspheres prepared in step 1) and add Tris buffer, stir mechanically, then add dopamine (DA), continue to stir the reaction, perform magnetic separation, collect the synthetic product Fe3O4@PDA, wash, perform magnetic separation, and dry to obtain Fe3O4@PDA microspheres;
[0026] 3) Preparation of Fe3O4@PDA-HDTMS microspheres
[0027] Take HDTMS and the Fe3O4@PDA microspheres prepared in step 2), add them to a container filled with methanol solution, and continue to stir the reaction; collect the synthetic product, wash, magnetically separate, and dry to obtain the magnetic hydrophobic material Fe3O4@PDA-HDTMS, namely Fe3O4@PH magnetic microspheres.
[0028] In one embodiment, the mass ratio of FeCl3·6H2O to ammonium acetate in step 1) is 1.35:(3.6-4), and can be specifically 1.35:3.85.
[0029] In one embodiment, the mass ratio of FeCl3·6H2O to sodium citrate in step 1) is 1.35:(0.2-0.6), and can be specifically 1.35:0.4.
[0030] In one embodiment, the mass volume ratio of the FeCl3·6H2O and ethylene glycol in step 1) is 1.35 g: (60-80) mL, and can be specifically 1.35 g: 70 mL.
[0031] In one embodiment, the reaction conditions in the high pressure reactor in step 1) are: temperature of 180-200° C., and reaction time of 16-24 h.
[0032] In one embodiment, the washing in step 1) is performed by alternating ultrapure water and anhydrous ethanol, and specifically, washing with ultrapure water for 3 to 5 times and washing with anhydrous ethanol for 3 to 5 times.
[0033] In one embodiment, the mass volume ratio of the Fe3O4 microspheres and the Tris-HCl buffer solution in step 2) is 80 mg: (30-50) mL, and can be specifically 80 mg: 40 mL.
[0034] In one embodiment, the pH of the Tris-HCl buffer solution in step 2) is 8.5 and the concentration is 0.01 mol / L.
[0035] In one embodiment, the mass ratio of Fe3O4 and DA in step 2) is 1:1.
[0036] In one embodiment, the stirring reaction conditions in step 2) are as follows: temperature is 25-30° C. and time is 12-24 h.
[0037] In one embodiment, the washing in step 2) is performed by alternating ultrapure water and anhydrous ethanol, and specifically, washing with ultrapure water for 3 to 5 times and washing with anhydrous ethanol for 3 to 5 times.
[0038] In one embodiment, the mass volume ratio of Fe3O4@PDA and HDTMS in step 3) is 60 mg: (0.45-0.6) mL, and can be specifically 60 mg: 0.5 mL.
[0039] In one embodiment, the preparation of the AgNPs suspension in step (2) includes the following steps: weighing AgNO3 powder, dissolving it in water, and heating it in a round-bottom flask. After boiling, quickly adding trisodium citrate and reacting it, cooling it to room temperature, filtering it, and storing it.
[0040] In one embodiment, the AgNO3 concentration obtained by dissolving the AgNO3 powder in water is 0.18 g / L.
[0041] In one embodiment, the heating temperature is 120-130°C.
[0042] In one embodiment, the mass fraction of trisodium citrate is 1-5%.
[0043] In one embodiment, the concentration of the NaCl solution in step (2) is 1-2 mol / L.
[0044] In one embodiment, the volume ratio of the diluent in step (2) to the AgNPs suspension and the NaCl solution is 50-100:10-30:3-6.
[0045] In one embodiment, the light induction parameters of step (2) are: select a 785nm laser, 80% to 100% laser energy, 120 to 130mW laser power, and focus a 50× objective lens on the sample for 50 to 80s; then turn off the laser.
[0046] In one embodiment, the Raman detection conditions in step (2) are: Raman spectroscopy analysis is performed using a microscopic confocal Raman spectrometer, with a spectral resolution of ≤0.65 cm -1 Sensitivity: The signal-to-noise ratio of the silicon third-order peak is better than 15:1. The sample is observed with a 50× objective lens, a 532nm laser is used, and the spectrum acquisition range is set at 200-3500cm -1 The spectrum accumulation was set to 30 s, and the laser intensity and exposure rate were adjusted in the range of 0.1 to 10.0 mW and 30 to 1 Hz, respectively.
[0047] In one embodiment, the reference Raman database in step (2) includes any one of the built-in spectral library of KnowItAll software, the SLoPP and SLoPP-E Raman spectral libraries, and the RDWP MP Raman database developed for studying MNPs.
[0048] The present invention also provides a method for quantitatively detecting MNPs in a sample based on photoinduced enhanced Raman spectroscopy, the method comprising the following steps:
[0049] Fe3O4@PH magnetic microspheres are added to the sample solution to be tested and stirred. Then, the Fe3O4@PH magnetic microspheres adsorbed with MNPs are collected under an external magnetic field and dried. The dried Fe3O4@PH magnetic microspheres adsorbed with MNPs are diluted with ultrapure water to form a dilution solution. The dilution solution is stirred and mixed with the AgNPs suspension and the NaCl solution to form a mixed solution. The mixed solution is dropped onto a glass slide for light induction and Raman detection is performed after drying. The content of MNPs in the sample to be tested is calculated based on a quantitative relationship model constructed based on the concentration of the MNPs standard solution and the spectral data of the corresponding standard characteristic peaks.
[0050] In one embodiment, the MNPs include one or more of polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polyamide (PA), polystyrene (PS), and polyethylene terephthalate (PET).
[0051] In one embodiment, the quantitative relationship model is constructed as follows:
[0052] A series of MNPs standard solutions are prepared using ultrapure water; Fe3O4@PH magnetic microspheres are then added to the series of MNPs standard solutions and stirred; Fe3O4@PH magnetic microspheres adsorbed with MNPs are then collected under an external magnetic field, dried, and the dried Fe3O4@PH magnetic microspheres adsorbed with MNPs are diluted with ultrapure water to form a dilution solution;
[0053] The diluent is stirred and mixed with the AgNPs suspension and the NaCl solution to form a mixed solution; the mixed solution is dropped onto a glass slide for light induction, the sample is collected, and Raman detection is performed after drying; a quantitative relationship model is established based on the concentration of the MNPs standard solution and the spectral data of the corresponding characteristic peaks of the standard.
[0054] In one embodiment, the characteristic peak is selected as follows: PE is 1295±5cm -1 , PP is 809±5cm -1 , PS is 1001±5cm -1 , PVC is 638±5cm -1 , PET is 1615±5cm -1 , PA is 1637±5cm -1 .
[0055] In one embodiment, the sample to be tested is any one of bottled drinking water, tap water, sea water, and a suspension of a digested human tissue sample.
[0056] The present invention also provides the application of the above-mentioned quantitative detection method and qualitative detection method in environmental system monitoring and management.
[0057] Beneficial effects:
[0058] (1) The PIERS method established in the present invention successfully achieved the quantitative and visual detection of polyethylene nanoplastics (PE-NPs) and polypropylene nanoplastics (PP-NPs) in aqueous solution, with detection limits of 5 and 10 μg / mL, respectively.
[0059] (2) The PIERS method established in the present invention has high sensitivity and achieves an additional enhancement of up to 13.2 times of the normal SERS signal for PE-NPs and up to 9.7 times of the normal SERS signal for PP-NPs.
[0060] (3) The PIERS method established in the present invention can identify PE, PP, PS, and PET nanoparticles in bottled drinking water, tap water, simulated seawater, and digested human tissue suspensions exposed to MNPs. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 Characterization images of Fe3O4@PH in Example 2, (A) SEM image, (B) TEM image, (C) contact angle image, (D) FT-IR image, (E) XPS image, (F) VSM image;
[0062] Figure 2 This is the PIAP principle diagram in Example 3;
[0063] Figure 3 The linear regression curves of PE-500 and PP-500 in Example 4 are shown in FIG. 4; (A) PE-500, (B) PP-500;
[0064] Figure 4 Comparison of PIERS performance using Fe3O4@PH as substrate in Example 5, where F@PH is Fe3O4@PH;
[0065] Figure 5 The enhancement factor effect diagram of PE-500 and PP-500 in Example 5; (A) PE-500, (B) PP-500;
[0066] Figure 6 This is a flow chart of PIERS detection in Example 6;
[0067] Figure 7 The Raman spectra of representative MNPs in bottled water, tap water, and simulated seawater samples in Example 6;
[0068] Figure 8 is a Raman spectrum of PE detected in the human tissue sample in Example 7;
[0069] Fig. 9 This is the EDX characterization diagram of PE in the human sample in Example 8, (A) EDX element map overlaying the SEM image; (B) Comparison of EDX spectra of two points in the carbon-rich and F@PH regions. DETAILED DESCRIPTION
[0070] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. The following specific implementation methods further describe the present invention.
[0071] The human tissues involved in the embodiments are fibroid tissues and uterine myometrium tissues of patients with uterine fibroids, which are derived from Wuxi Maternal and Child Health Hospital and the Affiliated Hospital of Jiangnan University, and are approved by the Medical Ethics Committee of the Affiliated Hospital of Jiangnan University (LS2021019). All participants signed informed consent forms.
[0072] PE-500 and PP-500 mentioned in the examples are abbreviations for PE particles with a size of 500 nm and PP particles with a size of 500 nm.
[0073] Example 1
[0074] A method for preparing a magnetic hydrophobic material Fe3O4@PDA-HDTMS comprises the following steps:
[0075] (1) Preparation of Fe3O4 microspheres
[0076] The magnetic Fe3O4 microspheres were synthesized by the solvent thermal reduction method: specifically, FeCl3·6H2O (1.35 g), NH4Ac (3.85 g), sodium citrate (0.4 g) and ethylene glycol (70 mL) were mixed in a flask, and mechanically stirred vigorously for 1 h to obtain a yellow solution; the obtained yellow solution was sealed in a 100 mL Teflon-lined autoclave, and placed in an oven at 200°C for 16 h, and after cooling to room temperature, the Fe3O4 magnetic microspheres were collected by magnetic separation (with an external magnet), and then washed alternately with ultrapure water and anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 h to obtain the magnetic Fe3O4 microspheres;
[0077] (2) Preparation of Fe3O4@PDA microspheres
[0078] Take 80 mg of the Fe3O4 microspheres obtained in step (1) and add 40 mL of Tris buffer (10 -2 mol / L, pH=8.5) and mechanically stirred for 20 min, then 80 mg of dopamine (DA) was transferred to the above solution and stirred continuously for 24 h. Finally, the synthesized product Fe3O4@PDA was collected by magnetic separation (with an external magnet), washed alternately with ultrapure water and anhydrous ethanol, magnetically separated and dried to obtain Fe3O4@PDA microspheres.
[0079] (3) Preparation of Fe3O4@PDA-HDTMS microspheres
[0080] Take 0.5 mL of hexadecyltrimethoxysilane (HDTMS: industrial grade, >85%, Sigma-Aldrich, catalog no. 52360) and 60 mg of Fe3O4@PDA microspheres synthesized in step (2), add them to a glass containing 30 mL of methanol solution, and shake them on a magnetic vortex mixer at room temperature overnight (12 h) to react; finally, collect the synthesized product Fe3O4@PDA-HDTMS by magnetic separation (external magnet), rinse it alternately with ultrapure water and anhydrous ethanol several times, and dry it at 60°C for 12 h to obtain Fe3O4@PDA-HDTMS microspheres, which are stored at low temperature. Fe3O4@PDA-HDTMS is abbreviated as Fe3O4@PH.
[0081] Performance Characterization
[0082] The magnetic microspheres Fe3O4 and Fe3O4@PDA and the magnetic hydrophobic material Fe3O4@PH prepared in Example 1 were characterized as follows:
[0083] The surface of Fe3O4@PH magnetic nanospheres was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Fourier transform infrared spectrometer (FT-IR) to verify the existence of certain characteristic functional groups and the synthesis of specific chemical bonds; the magnetic properties of Fe3O4, Fe3O4@PDA and Fe3O4@PH were measured by vibrating sample magnetometer (VSM) method at a magnetic field scanning intensity of -2T-2T and a temperature of 300K; X-ray photoelectron spectrometer (XPS) was used to perform qualitative analysis of the surface elements of Fe3O4@PH and structural analysis of chemical valence bonds; and the water contact angle of Fe3O4@PH microspheres was analyzed.
[0084] The characterization results are as follows Figure 1 As shown, Figure 1 A is the SEM characterization image of Fe3O4@PH, from which it can be observed that Fe3O4@PH is a spherical nanoparticle with a rough surface. Figure 1 B is the TEM characterization image of Fe3O4@PH. A clear shadow layer can be clearly seen on the outer layer of the Fe3O4@PH particles, proving that the material has a core-shell structure. Figure 1 C It can be found that the water contact angle of Fe3O4@PH is 139.6°, indicating that it has strong hydrophobicity, which can be attributed to the presence of HDTMS hydrophobic long chains on its surface. Figure 1 D and E help determine the successful synthesis of materials by characterizing the chemical bonds and chemical binding energy in the materials, respectively. Figure 1 F is the magnetic property characterization of the material. It can be found that with the sequential coating of PDA and HDTMS, the magnetism of the composite material will also decrease, which is a normal phenomenon. In addition, it is found that the magnetism of Fe3O4@PH is very good and meets the experimental requirements. All characterization results show that the material was successfully synthesized and has excellent magnetic properties and strong hydrophobicity.
[0085] Example 2
[0086] A method for preparing SERS substrate AgNPs comprises the following steps:
[0087] Weigh 0.018 g of AgNO3 powder and dissolve it in 100 mL of ultrapure water. Heat the AgNO3 solution in a 250 mL clean round-bottom flask. After the solution boils, quickly add 2.0 mL of 1% trisodium citrate and react for 1 h. Cool the solution naturally to room temperature and filter it through a 0.22 μm filter membrane to obtain uniform SERS substrate AgNPs, which are then stored in a 4 °C refrigerator away from light for later use.
[0088] Example 3
[0089] A method for qualitatively detecting MNPs based on Fe3O4@PH photoinduced enhanced Raman spectroscopy (PIERS) comprises the following steps:
[0090] (1) Photoinduced aggregation process (PIAP)
[0091] 10 mg of Fe3O4@PH magnetic microspheres were added as adsorbents to a 10 mL test solution and stirred at 120 rpm for 30 min. Then, Fe3O4@PH magnetic microspheres adsorbed with MNPs were collected under an external magnetic field and the solid was dried in an oven at 60 °C for 12 h. After mixing the Fe3O4@PH magnetic microspheres adsorbed with MNPs, 5 mg was diluted to 10 mL with ultrapure water, 800 μL of the dilution, 200 μL of AgNPs suspension and 50 μL of NaCl (1 mol / L) were mixed to form a mixed solution. 50 μL of the mixed solution was dropped on a glass slide, a 785 nm laser was selected, 100% laser energy, 130 mW laser power, and a 50× objective lens was focused on the sample for 60 s. Then the laser was turned off and waited for 10 s. After the bubbles disappeared, the sample was collected and dried for PIERS detection. The schematic diagram of the PIAP principle is shown in the figure. Figure 2 As shown;
[0092] (2) PIERS qualitative test
[0093] Raman spectroscopy was performed using a confocal Raman spectrometer (HORIBA Jobin Yvon SAS, France), with a spectral resolution of ≤0.65 cm -1 Sensitivity: The signal-to-noise ratio of the silicon third-order peak is better than 15:1. The sample is observed with a 50× objective lens, a 532nm laser is used, and the spectrum acquisition range is set at 200-3500cm -1 The spectrum accumulation was set to 30 s, and the laser intensity and exposure rate were adjusted in the range of 0.1 to 10.0 mW and 30 to 1 Hz, respectively;
[0094] Based on the KnowItAll software, the acquired Raman spectra were paired with the standard reference Raman database, and spectra with a similarity of more than 70% with the standard reference spectra were screened, indicating the presence of suspicious plastic polymers in the samples.
[0095] Example 4
[0096] A method for quantitatively detecting MNPs based on Fe3O4@PH light-induced enhanced Raman spectroscopy comprises the following steps:
[0097] (1) Construction of quantitative relationship model
[0098] Ultrapure water was used to prepare standard solutions of PE-500 with concentrations of 2, 5, 10, 20, 50 and 100 μg / mL, and standard solutions of PP-500 with concentrations of 5, 10, 20, 50, 100 and 200 μg / mL, respectively. 10 mg of Fe3O4@PH magnetic microspheres were added as adsorbents into 10 mL of the above series of concentration solutions, and stirred at 120 rpm for 30 min. Subsequently, Fe3O4@PH magnetic microspheres adsorbed with MNPs were collected under an external magnetic field and then dried in an oven at 60°C for 12 h.
[0099] The Fe3O4@PH magnetic microspheres adsorbed with MNPs in the above standard solution were mixed, and 5 mg was diluted to 10 mL with ultrapure water, and then 800 μL of the dilution, 200 μL of the AgNPs suspension prepared in Example 2 and 50 μL of NaCl (1 mol / L) were respectively taken and stirred and mixed; 50 μL of the mixed solution was dropped on a glass slide, and a 785 nm laser, 100% laser energy, 130 mW laser power, and a 50× objective lens were selected to focus on the sample for 60 seconds, then the laser was turned off, and waited for 10 seconds. After the bubbles disappeared, the samples were collected, dried, and subjected to PIERS detection;
[0100] Raman spectroscopy was performed using a confocal Raman spectrometer (HORIBA Jobin Yvon SAS, France), with a spectral resolution of ≤0.65 cm -1 Sensitivity: The signal-to-noise ratio of the silicon third-order peak is better than 15:1. The sample is observed with a 50× objective lens, a 532nm laser is used, and the spectrum acquisition range is set at 200-3500cm -1 The spectrum accumulation was set to 30 s, and the laser intensity and exposure rate were adjusted in the range of 0.1 to 10.0 mW and 30 to 1 Hz, respectively;
[0101] According to the obtained PIERS spectrum ( Figure 3 ), the Raman signal intensity of PE and PP gradually decreased in a concentration-dependent manner. When the concentration was as low as 5 μg / mL for PE and 10 μg / mL for PP, PIERS signals could still be obtained, indicating that the PIERS method with Fe3O4@PH and AgNPs as substrates has high sensitivity;
[0102] Based on 1295cm -1 and 809cm -1 The characteristic peaks correspond to the deformation vibration of CH2 of PE and the asymmetric stretching vibration of CH2 of PP, indicating its potential use as a quantitative curve for detecting PE and PP plastics in actual samples. According to the PIERS spectrum and the concentration of 5-200 μg / mL, the peak of PE-500 at 1295 cm -1The linear equation at is y = 4.97239x + 681.90553, R 2 =0.96498; PP-500 at 809cm -1 The linear equation at is y=6.25328x+617.99282, R 2 =0.96317;
[0103] (2) Determination of MNPs in spiked samples
[0104] Accurately weigh 0.021g, 0.022g, 0.021g of PE NPs, 0.022g, 0.019g, 0.021g of PP NPs, respectively, and put them into 50mL glass vials, and add 20mL of ultrapure water respectively. The mass concentrations are 1.05mg / mL, 1.10mg / mL, 1.05mg / mL for PE NPs; 1.10mg / mL, 0.95mg / mL, 1.05mg / mL for PP NPs; after diluting 20 times, the concentrations are 52.5μg / mL, 55.0μg / mL, 52.5μg / mL for PE NPs; 55.0μg / mL, 47.5μg / mL, 52.5μg / mL for PP NPs;
[0105] 10 mg of Fe3O4@PH magnetic microspheres were added as adsorbents to 10 mL of the above PE NPs and PPNPs dilutions, respectively, and stirred at 120 rpm for 30 min. Then, the Fe3O4@PH magnetic microspheres adsorbed with MNPs were collected under an external magnetic field and dried in an oven at 60 ° C for 12 h. After mixing the Fe3O4@PH magnetic microspheres adsorbed with MNPs, 5 mg was taken and diluted to 10 mL with ultrapure water, 800 μL of the dilution, 200 μL of AgNPs suspension and 50 μL of NaCl (1 mol / L) were taken and stirred to form a mixed solution; 50 μL of the mixed solution was dropped on a glass slide, and a 785 nm laser was selected, with 100% laser energy, 130 mW laser power, and a 50× objective lens focused on the sample for 60 s; then the laser was turned off, and after waiting for 10 s, the sample was collected after the bubbles disappeared, and PIERS detection was performed after drying;
[0106] According to the quantitative relationship model constructed in step (1), the content of MNPs in the sample to be tested is calculated; the test results are: the detection concentration of the two actual samples of PE and PP, the PE NPs spike recovery rate is 80.6% to 85.8%, RSD≤2.1%; the PP NPs spike recovery rate is 80.3% to 84.4%, RSD≤1.8%.
[0107] Example 5 PIERS performance of Fe3O4@PH as substrate
[0108] The detection performance of PIERS was verified by detecting 100 μg / mL of PE-500 nanoplastics using different test conditions.
[0109] 1. Raman detection of PE-500: Referring to Example 3, the test solution in step (1) was adjusted to a 100 μg / mL PE-500nm aqueous solution, 50 μL was dropped on a glass slide and dried, and then Raman detection was performed according to the PIERS qualitative detection technology in step (2) of Example 3.
[0110] 2. PIAP detection of PE-500+Fe3O4@PH: Referring to Example 3, the test solution in step (1) was adjusted to a 100 μg / mL PE-500 aqueous solution, and “take 800 μL of dilution, 200 μL of AgNPs suspension and 50 μL of NaCl (1 mol / L) and stir to form a mixed solution” was changed to “take 800 μL of dilution”. The other parameters and conditions were consistent with step (1) of Example 3. Raman detection was performed according to the PIERS qualitative detection technology in step (2).
[0111] 3. SERS detection of PE-500+AgNPs: Referring to Example 3, step (1) was adjusted to take 800 μL of 100 μg / mL PE-500 aqueous solution, 200 μL of AgNPs suspension and 50 μL of NaCl (1 mol / L), stir and mix to form a mixed solution, take 50 μL and drop it on a glass slide and dry it, then perform SERS detection according to the PIERS qualitative detection technology in step (2).
[0112] 4. SERS detection of PE-500+Fe3O4@PH+AgNPs: Referring to Example 3, the test solution in step (1) was adjusted to a 100 μg / mL PE-500 aqueous solution, and “select 785 nm laser, 100% laser energy, 130 mW laser power, 50× objective lens focusing on the sample for 60 s; then turn off the laser, wait 10 s, and collect the sample after the bubbles disappear, and dry it” was adjusted to “perform PIERS detection after natural drying;” the other parameters and conditions were consistent with step (1) of Example 3, and SERS detection was performed according to the PIERS qualitative detection technology in step (2).
[0113] 5. PIERS detection of PE-500+Fe3O4@PH+AgNPs: Referring to Example 3, the test solution in step (1) was adjusted to a 100 μg / mL PE-500 aqueous solution, and the other parameters and conditions were consistent with step (1) of Example 3. PIERS detection was performed according to the PIERS qualitative detection technology in step (2).
[0114] Test results such as Figure 4 As shown in the figure, by analyzing the obtained Raman spectra, it can be seen that the characteristic peak signal intensity of PE after PIAP treatment is significantly higher than the Raman spectrum signal of original PE. This shows that after PIAP treatment, the Raman signal will be enhanced. However, the Raman intensity of the PE spectrum signal after PIAP treatment is weaker than that of the SERS (substrate is only AgNPs) signal.
[0115] It can be seen that Fe3O4@PH has the effect of light-induced concentration of target molecules, but its role in enhancing the SERS signal is limited. By comparing SERS (the substrate is Fe3O4@PH and AgNPs, but no PIAP treatment) detection and PIERS (the substrate is Fe3O4@PH and AgNPs, PIAP treatment) detection, it can be clearly observed that the Raman signal of PE-500nm PIERS detection has a significant enhancement. This result shows that PIAP can further concentrate and enrich MNPs particles, playing a role in additionally enhancing the SERS signal. This confirms that PIERS has excellent PIERS performance for micro-nano plastic detection.
[0116] In addition, the enhancement factor (EF) was calculated to quantitatively evaluate the performance of Fe3O4@PH magnetic microspheres with AgNPs as substrate. The intensity of the characteristic peaks of PE-500 and PP-500 particles on PIERS substrate and SERS substrate was investigated, where the SERS substrate was recorded as non-PIERS substrate and used as the calculation equation of the additional enhancement factor:
[0117]
[0118] Among them I PIERS and I SERS Represents the intensity of the characteristic peaks of PE-500 and PP-500 particles on PIERS substrate and SERS substrate, respectively; N PIERS and N SERS are the number of molecules on the laser spot on the PIERS substrate and the SERS substrate, respectively.
[0119] The concentrations of PE-500 and PP-500 used and the selected areas to be tested were the same. PIERS and N SERS It can be set to 1. In order to eliminate the influence on Raman intensity, the integration time and laser power are kept unchanged.
[0120] The concentration of sample PE-500 was 100 μg / mL, the concentration of PP-500 was 200 μg / mL, 5 points were randomly selected from each sample, and the rest were consistent with Example 3 for testing.
[0121] Test results such as Figure 5 As shown, from Figure 5 It can be seen that: Figure 5 A and Figure 5 B shows the PE-500 at 1065 cm -1 、1130cm -1 、1095cm -1 、1440cm -1 and PP-500 at 398cm -1 、809cm -1 、841cm -1 、1152cm -1 、1330cm -1 、1458cm -1 Enhancement factor: The maximum enhancement factor of PE-500 reaches 13.2, and the maximum enhancement factor of PP-500 reaches 9.7.
[0122] Example 6
[0123] A method for detecting MNPs in an aqueous solution based on Fe3O4@PH light-induced enhanced Raman spectroscopy comprises the following steps:
[0124] (1) Four types of commercially available bottled water (Wahaha, Nongfu Spring, Yibao and Binglu), tap water and simulated seawater were first filtered through a glass fiber filter membrane with a pore size of 1 μm to remove large particles and obtain the water samples to be tested;
[0125] (2) 30 mL of the water sample obtained in step (1) was placed in a 50 mL glass beaker, 30 mg of Fe3O4@PH magnetic microspheres were added, and the mixture was stirred at 120 rpm for 30 min. Subsequently, the Fe3O4@PH magnetic microspheres adsorbed with MNPs were collected under an external magnetic field;
[0126] (3) PIERS detection was performed with reference to Example 3 (PIERS detection process is as follows Figure 6 shown).
[0127] Test results such as Figure 7 As shown, the results showed that MNPs were detected in commercially available bottled drinking water, tap water and simulated seawater, and the main types of MPs contained were PE, PP and PET.
[0128] Example 7 PIERS detection of MNPs in human samples
[0129] The bottled water, tap water and simulated seawater in Example 6 were adjusted to be the digested human tissue sample suspension, and the other conditions were kept the same as in Example 6 for testing. Figure 8As shown, the results showed that MNPs were detected in the suspension of digested human tissue samples, and the main types of MNPs contained were PE and PP.
[0130] Furthermore, samples in which PE-NPs were detected using PIERS were selected and further characterization tests were performed on the test results using EDX. Fig. 9 As shown, the EDX element mapping of the PIAP point shows several carbon-rich areas, and the scanning electron microscope shows that these particles are particles with a certain size less than 1μm. The measured PIERS spectrum has several peaks that match the reference peaks of PE, indicating that the small particles tested in the carbon-rich area are PE particles.
[0131] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for qualitatively detecting MNPs in a sample based on Fe3O4@PH light-induced enhanced Raman spectroscopy, characterized in that: The method comprises the following steps: (1) Preparation of samples to be tested The Fe3O4@PH magnetic microspheres are added to the sample solution to be tested and stirred, and then the Fe3O4@PH magnetic microspheres adsorbed with MNPs are collected under an external magnetic field, dried, and the dried Fe3O4@PH magnetic microspheres adsorbed with MNPs are diluted with ultrapure water to form a dilution solution; (2) Qualitative analysis of samples to be tested The diluted solution obtained in step (1) is mixed with the AgNPs suspension and the NaCl solution to form a mixed solution; the mixed solution is dropped onto a glass slide for light induction, and Raman detection is performed after drying; Based on the KnowItAll software, the acquired Raman spectra were paired with the standard reference Raman database, and spectra with a similarity of more than 70% with the standard reference spectra were screened, indicating the presence of MNPs in the sample.
2. The method according to claim 1, characterized in that The sample to be tested is any one of bottled drinking water, tap water and sea water.
3. The method according to claim 1, characterized in that The preparation of the Fe3O4@PH magnetic microspheres in step (1) comprises the following steps: 1) Preparation of Fe3O4 microspheres FeCl3·6H2O, ammonium acetate, sodium citrate and ethylene glycol are mixed in a flask, and mechanically stirred to completely mix to obtain a yellow solution; the yellow solution is sealed in a high-pressure reactor to react; after the reaction, it is cooled, washed, magnetically separated and dried to obtain Fe3O4 microspheres; 2) Preparation of Fe3O4@PDA microspheres Take the magnetic Fe3O4 microspheres prepared in step 1) and add Tris buffer, stir mechanically, then add dopamine, continue to stir the reaction, perform magnetic separation, collect the synthetic product Fe3O4@PDA, wash, perform magnetic separation, and dry to obtain Fe3O4@PDA microspheres; 3) Preparation of Fe3O4@PDA-HDTMS microspheres HDTMS and the Fe3O4@PDA microspheres prepared in step 2) are added to a container containing a methanol solution and continuously stirred for reaction; the synthesized product is collected, washed, magnetically separated, and dried to obtain Fe3O4@PH magnetic microspheres.
4. The method according to claim 1, characterized in that: The light induction parameters of step (2) are: selecting a 785nm laser, 80% to 100% laser energy, 120 to 130mW laser power, and focusing a 50× objective lens on the sample for 50 to 80 seconds; then turning off the laser.
5. The method according to claim 1, characterized in that The Raman detection conditions in step (2) are as follows: Raman spectroscopy analysis is performed using a micro-confocal Raman spectrometer, with a spectral resolution of ≤0.65 cm -1 Sensitivity: The signal-to-noise ratio of the silicon third-order peak is better than 15:
1. The sample is observed with a 50× objective lens, a 532nm laser is used, and the spectrum acquisition range is set at 200-3500cm -1 The spectrum accumulation was set to 30 s, and the laser intensity and exposure rate were adjusted in the range of 0.1 to 10.0 mW and 30 to 1 Hz, respectively.
6. The method according to claim 1, characterized in that The reference Raman database in step (2) includes any one of the built-in spectral library of KnowItAll software, SLoPP and SLoPP-E Raman spectral libraries, and the RDWP MP Raman database developed for studying MNPs.
7. A method for quantitatively detecting MNPs in a sample based on photoinduced enhanced Raman spectroscopy, characterized in that: The method comprises the following: Fe3O4@PH magnetic microspheres are added to the sample solution to be tested and stirred. Then, the Fe3O4@PH magnetic microspheres adsorbed with MNPs are collected under an external magnetic field and dried. The dried Fe3O4@PH magnetic microspheres adsorbed with MNPs are diluted with ultrapure water to form a dilution solution. The dilution solution is stirred and mixed with the AgNPs suspension and the NaCl solution to form a mixed solution. The mixed solution is dropped onto a glass slide for light induction and Raman detection is performed after drying. The content of MNPs in the sample to be tested is calculated based on a quantitative relationship model constructed based on the concentration of the MNPs standard solution and the spectral data of the corresponding standard characteristic peaks.
8. The method according to claim 7, characterized in that The MNPs include one or more of polyethylene PE, polypropylene PP, polyvinyl chloride PVC, polyamide PA, polystyrene PS, and polyethylene terephthalate PET.
9. The method according to claim 7, characterized in that: The characteristic peaks of the MNPs standard are as follows: PE is 1295±5cm -1 , PP is 809±5cm -1 , PS is 1001±5cm -1 , PVC is 638±5cm -1 , PET is 1615±5cm -1 , PA is 1637±5cm -1 .
10. Application of the qualitative detection method according to any one of claims 1 to 6 and the quantitative detection method according to any one of claims 7 to 9 in environmental system monitoring and management.